Understanding e-government (G2C) in the knowledge society. (11th June 2007) - Kolsaker, Ailsa
Governments are investing heavily both politically and financially in the knowledge society as a route to economic growth and international competitiveness. Web technology provides an efficient, cost-effective platform for national knowledge management, with e-government in particular being welcomed as means of engaging citizens directly in knowledge creation and dissemination. The discourse of the knowledge society assumes a robust enabling role for government, downplaying its declining role in national policymaking and possible divergence of 'public' and 'national' interests. Additionally, in conceptualising e-government as a facilitator of the knowledge society, governments tend to underplay the significance of entrenched cultural and operational barriers in public sector bureaucracy and citizens' reluctance to engage. This paper argues that it is only by factoring in such complexities that governments can truly understand e-government in the knowledge society and proposes the adoption of well-established marketing practices to provide pragmatic, user-centric approaches to knowledge-driven citizen engagement.